Pretreatment of Corn Stover Using an Extremely Low-Liquid Ammonia (ELLA) Method for the Effective Utilization of Sugars in Simultaneous Saccharification and Fermentation (SSF) of Ethanol - Le, Tin Diep Trung; Nguyen Truong, Vi Phuong; Ngo, My Thi Tra; Kim, Tae Hyun; Oh, Kyeong Keun (Fermentation (Basel), 2021)
Extremely low-liquid ammonia (ELLA) pretreatment using aqueous ammonia was investigated in order to enhance the enzymatic saccharification of corn stover and subsequent ethanol production. In this study, corn stover was treated with an aqueous ammonia solution at different ammonia loading rates (0.1, 0.2, and 0.3 g NH3/g biomass) and various liquid-to-solid (L/S) ratios (0.55, 1.12, and 2.5). The ELLA pretreatment was conducted at elevated temperatures (90–150 °C) for an extended period (24–120 h). Thereafter, the pretreated material was saccharified by enzyme digestion and subjected to simultaneous saccharification and fermentation (SSF) tests. The effects of key parameters on both glucan digestibility and xylan digestibility were analyzed using analysis of variance (ANOVA). Under optimal pretreatment conditions (L/S = 2.5, 0.1 g-NH3/g-biomass, 150 °C), 81.2% glucan digestibility and 61.1% xylan digestibility were achieved. The highest ethanol yield achieved on the SSF tests was 85.4%. The ethanol concentration was 14.5 g/L at 96 h (pretreatment conditions: liquid-to-solid ratio (L/S) = 2.5, 0.1 g-NH3/g-biomass, 150 °C, 24 h. SSF conditions: microorganism Saccharomyces cerevisiae (D5A), 15 FPU/g-glucan, CTech2, 3% w/v glucan, 37 °C, 150 rpm).